The Influence of Social Media Marketing on Purchase Intention - Mauliza, Fazia; Fadhilla, Hanifa Nur (LifeSciFi, 2025)
The Indonesian skincare industry has experienced significant growth, largely driven by technological innovations and the widespread use of social media as a key marketing tool. This study examines how social media marketing influences consumer purchase intention for Somethinc products, with a particular focus on the mediating effects of brand trust and brand image. Somethinc's strategy of leveraging visually appealing content across its social media platforms is identified as a competitive advantage. Adopting a quantitative approach, the study gathered data from 170 respondents, including both loyal and potential Somethinc customers, via a structured questionnaire. The data were analyzed using Structural Equation Modeling (SEM) through SmartPLS. The findings reveal that social media marketing has a positive impact on brand trust and brand image, which, in turn, significantly affect purchase intention. However, no direct effect was found between social media marketing or brand image and purchase intention. This suggests that while social media marketing may not directly lead to purchases, it plays a crucial role in shaping brand perceptions, which ultimately influence consumer buying behavior. These insights are valuable for skincare brands looking to refine their digital marketing strategies and boost consumer engagement in the highly competitive digital marketplace.